Gen Z Employees’ Adaptive Performance in Hybrid Workplaces: The Role of Inclusive Leadership, Creativity, and Work Engagement - Κatsaros, Kleanthis K. (The Journal of applied behavioral science, 2025)
By drawing on the social exchange theory, the article suggests a moderated mediation model to examine the role of employee creativity and work engagement in the relationship between inclusive leadership and employee adaptive performance. Data were collected from 305 Gen Z employees in the Greek telecommunication industry and their supervisors in three sequential phases. The research findings suggest that employee creativity mediates the relationship between inclusive leadership and employee adaptive performance. Additionally, they provide support that work engagement moderates the relationship between employee creativity and adaptive performance, as well as, the indirect relationship between inclusive leadership and employee adaptive performance through employee creativity; such that the positive relationships are stronger when work engagement is higher. The results indicate that should leaders and change management practitioners manage to positively influence (Gen Z) employees’ creativity by employing inclusive strategies and procedures; they will boost their adaptive performance during change.